DEVELOPMENT OF A FUZZY LOGIC BASED MODEL FOR CORROSION UNDER INSULATION IN PIPING SYSTEMS - KHAN, MUHAMMAD MOHSIN (2017)
Corrosion Under Insulation (CUI) is found to be a major problem for insulated piping systems in oil and gas industries including refineries, petrochemical companies and gas processing plants. As these insulated piping systems carry hydrocarbons or other acidic process fluids, gradual thinning in these piping systems takes place which causes these pipes to be leak or rupture or in a worst scenario leads towards a hazardous situation.